Do financial consultants exert a moderating effect on savings behavior?A study on the Indian rural population - Giridhari Mohanta; Ashutosh Dash (Cogent Economics & Finance)
Access to basic financial services, though, enables destitute and vulnerable individuals in society to promote prosperity, a significant section of rural population is still unbanked in India. Unveiling various small saving schemes, the Indian Government has accelerated the financial inclusion, but the availability of numerous alternative schemes has created a surplus of market information, causing difficulty in building economic judgment for the rural people having no financial socialization through formal and informal education and training. While dismissive investors rely on their own decisions, the convincing behaviour of financial consultants may play a crucial role in shaping the saving habits of the preoccupied population. To analyse the moderation effect of financial consultants on the relationship between small savings schemes, financial literacy and behaviour, and savings habit of rural people, the empirical study employs a two-phase structural equation modelling on the data gathered from 343 adult respondents from 12 Indian districts with a considerable rural population. In order to validate the hypothesized measurement model, a confirmatory factor analysis is carried out and in the next phase, the structural model is used to verify the association between exogenous and endogenous variables. The study exhibits a significant positive impact of predictors and moderation variables on the savings habit. The study recommends integrating consultants into the financial engineering process to advance inclusivity and encourage saving behaviour of rural individuals for personal and economic prosperity.